2007
DOI: 10.1016/j.bbr.2006.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic background and environmental novelty on wheel running as a rewarding behaviour in mice

Abstract: Recent studies suggest running wheel activity to be naturally rewarding and reinforcing; considering the shared neuro-behavioural characteristics with drug-induced reward situations, wheel running behaviour gains interest as a tool to study mechanisms underlying reward-sensitivity. Previously, we showed that wheel running has the potential to disrupt the daily organization of home cage behaviour in female C57BL/6 [de Visser L, van den Bos R, Spruijt BM. Automated home cage observations as a tool to measure the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 34 publications
6
37
1
Order By: Relevance
“…Evidence of the rewarding and potentially addictive properties of running wheel is currently accumulating. Rodents, in fact, are highly motivated to gain access to running wheels and display CPP to an environment associated with wheel running (Iversen, 1993;Belke, 1997;Lett et al, 2000;de Visser et al, 2007). Furthermore, animals that run long distances daily show withdrawal signs when access to the running wheels is denied (Hoffmann et al, 1987), and display increased vulnerability for cocaine self-administration and reinstatement after abstinence (Larson and Carroll, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of the rewarding and potentially addictive properties of running wheel is currently accumulating. Rodents, in fact, are highly motivated to gain access to running wheels and display CPP to an environment associated with wheel running (Iversen, 1993;Belke, 1997;Lett et al, 2000;de Visser et al, 2007). Furthermore, animals that run long distances daily show withdrawal signs when access to the running wheels is denied (Hoffmann et al, 1987), and display increased vulnerability for cocaine self-administration and reinstatement after abstinence (Larson and Carroll, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents, for example, show CPP to an environment associated with wheel running (Iversen, 1993;Belke, 1997;Lett et al, 2000;de Visser et al, 2007), and show withdrawal signs when access to the running wheels is denied (Hoffmann et al, 1987). The rewarding properties of sucrose drinking are less extensively investigated (Lenoir et al, 2007).…”
Section: Rewarding Properties Of Sucrose and Of Exercise In Micementioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6J female mice were chosen for this experiment because they consistently consume higher amounts of alcohol and display higher levels of wheel running as compared with C57BL/6J males (Belknap et al, 1993;de Visser et al, 2007). Fifteen female mice were group housed three or four to a standard mouse cage (19.05 × 31.75 × 12 cm).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…These results are in agreement with data reported by Jung et al (2006), indicating that wheel running in (distance and duration) is stable for at least 15 weeks in C57BL/6J mice. It has been shown that intermittent wheel availability or periods of alternating access do not induce a rebound effect on running distance in C57BL/J mice (de Visser et al, 2007).…”
Section: Wheel Access Modifies Ethanol Drinking Patternsmentioning
confidence: 99%